2014
DOI: 10.1016/j.febslet.2014.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Removal of both Ycf48 and Psb27 in Synechocystis sp. PCC 6803 disrupts Photosystem II assembly and alters QA oxidation in the mature complex

Abstract: a b s t r a c tThe Photosystem II (PS II) assembly factors Psb27 and Ycf48 are transiently associated with PS II during its biogenesis and repair pathways. We investigated the function of these proteins by constructing knockout mutants in Synechocystis sp. PCC 6803. In DYcf48 cells, PS II electron transfer and stable oxygen evolution were perturbed. Additionally, Psb27 was required for photoautotrophic growth of cells lacking Ycf48 and assembly beyond the RC47 assembly complex in DYcf48:DPsb27 cells was impede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 45 publications
4
39
0
Order By: Relevance
“…Our results also point to a functional connection, since the expression profile for psb27 closely resembled that of slr0171 ( ycf37 ) ( Fig. S10 ; cluster J), for which the corresponding protein contributes to assembly and stabilization of PSI complexes 45 46 . Likewise, the co-transcription of psbN with genes encoding core subunits of both PSII and PSI ( Fig.…”
Section: Discussionsupporting
confidence: 59%
“…Our results also point to a functional connection, since the expression profile for psb27 closely resembled that of slr0171 ( ycf37 ) ( Fig. S10 ; cluster J), for which the corresponding protein contributes to assembly and stabilization of PSI complexes 45 46 . Likewise, the co-transcription of psbN with genes encoding core subunits of both PSII and PSI ( Fig.…”
Section: Discussionsupporting
confidence: 59%
“…Those results clearly demonstrated that enhanced ROS production can be a direct consequence of an impaired PSII repair cycle with implications for virusinduced suppression of ftsH expression in our study. Other research conducted on HCF136 knockouts in Synechocystis demonstrated an enhanced susceptibility to photodamage, which is thought to arise from compromised PSII reaction centers produced by an impaired assembly pathway (Jackson et al 2014). PSII photoinhibition and repair is also thought to be one strategy to protect PSI from irreversible damage (Tikkanen et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This data collection procedure enabled normalization of the spectrum at 580 nm to the fluorescein peak observable only in the excitation spectrum at 440 nm. Variable chlorophyll a fluorescence relaxation and induction measurements were performed at room temperature as described by Jackson et al (26). For the derivation of the phycobilisome-to-PSII energy transfer capacity, we took F(J) to be the fluorescence maximum occurring after approximately 2.5 ms of actinic illumination; the amplitude of this point for the blue measuring flash data correlated with the variable fluorescence (F V ) determined from the single-turnover fluorescence relaxation experiments.…”
Section: Methodsmentioning
confidence: 99%